La dependencia: un nuevo riesgo de la seguridad social chilena - Arellano Ortiz, Pablo (2018)
The protection of old age has become a constant concern in recent years. Within this, the protection of dependent adults is presented as a new social risk for social security. This approach is the one addressed in this work, for which the French model of dependency protection is used. It is argued that Chilean security can follow this approach. It is considered necessary to be able to identify and analyze the elements of dependency benefits of the French legislation that allow sustaining that the dependency can be protected by the Chilean social security system. The elements presented will allow the development of a more informed debate about the protection of an increasing group in Chile.